Screening of genes of proteins interacting with p7 protein of hepatitis C virus from human liver cDNA library by yeast two-hybrid system - Huang, Yan-Ping (World J Gastroenterol, 2005)
AIM: To investigate the biological function of p7 protein and to look for proteins interacting with p7 protein in hepatocytes. METHODS: We constructed p7 protein bait plasmid by cloning the gene of p7 protein into pGBKT7, then transformed it into yeast AH109 (a type). The transformed yeast was mated with yeast Y187 (α type) containing liver cDNA library plasmid, pACT2 in 2 × YPDA medium. Diploid yeast was plated on synthetic dropout nutrient medium (SD/-Trp-Leu-His-Ade) containing x-α-gal for selection and screening. After extracting and sequencing of plasmids from blue colonies, we performed sequence analysis by bioinformatics. RESULTS: Fifty colonies were selected and sequenced. Among them, one colony was Homo sapiens signal sequence receptor, seven colonies were Homo sapiens H19, seven colonies were immunoglobulin superfamily containing leucine-rich repeat, three colonies were spermatid peri-nuclear RNA binding proteins, two colonies were membrane-spanning 4-domains, 24 colonies were cancer-associated antigens, four colonies were nucleoporin 214 ku and two colonies were CLL-associated antigens. CONCLUSION: The successful cloning of gene of protein interacting with p7 protein paves a way for the study of the physiological function of p7 protein and its associated protein.